Efficacy and safety of immune checkpoint inhibitors in the treatment of recurrent or metastatic nasopharyngeal carcinoma: A systematic review and meta-analysis - Zhixin Yu; Shaodong Hong; Hui Yu; Xuanye Zhang; Zichun Li; Ping Chen; Yixin Zhou; Jing Ni (Chinese Medical Journal)
Abstract. Background:. The combination of immune checkpoint inhibitors and chemotherapy (ICI + Chemo) shows promise in treatment of recurrent or metastatic nasopharyngeal carcinoma (RM-NPC), but some patients received limited benefit and the prognostic factors of the treatments remain unclear. Furthermore, ICIs efficacy in subsequent treatments needs further evaluation. Methods:. A systematic search on PubMed, Embase, the Cochrane Library, and major conference proceedings was conducted to identify relevant studies for meta-analysis. The study was designed to compare ICI + Chemo with chemotherapy in first-line treatment and identify efficacy predictors, and to evaluate ICIs alone in subsequent-line treatment for RM-NPC, with a focus on progression-free survival (PFS), objective response rate (ORR), and treatment-related adverse events (AEs). Results:. Fifteen trials involving 1928 patients were included. Three trials compared ICI + Chemo with chemotherapy as a first-line treatment, while 12 trials evaluated ICIs alone in subsequent-line treatment of RM-NPC patients. First-line ICI + Chemo showed superior PFS (hazard ratio [HR] = 0.52, 95% confidence interval [CI], 0.43–0.63; P <0.001) and ORR (risk ratio [RR] = 1.14, 95% CI, 1.05–1.24; P <0.001) compared to chemotherapy, without increased AEs (RR = 1.01, 95% CI, 0.99–1.03; P = 0.481). Neither programmed death-ligand 1 (PD-L1) nor other factors predicted the efficacy of ICI + Chemo vs. chemotherapy. Subsequent-line ICIs alone had a median PFS of 4.12 months (95% CI, 2.93–5.31 months), an ORR of 24% (95% CI, 20–28%), with grade 1–5/grade 3–5 AEs at 79%/14%. However, ICIs alone were associated with significantly shorter PFS (HR = 1.31, 95% CI, 1.01–1.68; P = 0.040) than chemotherapy alone. Conclusions:. ICI + Chemo confers superior survival benefits compared to chemotherapy in first-line RM-NPC treatment, independent of PD-L1 expression or other factors. However, ICIs alone demonstrate a manageable safety profile but do not surpass chemotherapy in efficacy for subsequent-line treatment.